Losing control how and why people fail at self-regulation - Baumeister, Roy F. 1953-; Heatherton, Todd F.; Tice, Dianne M. (Acad. Press, 1994)
The consequences of these self-control problems go beyond individuals to affect family members and society at large. In Losing Control, the authors provide a single reference source with comprehensive information on general patterns of self-regulation failure across contexts, research findings on specific self-control disorders, and commentary on the clinical and social aspects of self-regulation failure. Self-control is discussed in relation to what the "self" is, and the cognitive, motivational, and emotional factors that impinge on one's ability to control one's "self.